Experimental exposure to low concentrations of Neoparamoebaperurans induces amoebic gill disease in Atlantic salmon. Issue 7 (8th March 2021) - Bridle, Andrew R.; Hill, Thomas; Smith, Aaron; Crosbie, Philip; Nowak, Barbara F.
Abstract: Amoebic gill disease (AGD) is a significant issue in Atlantic salmon mariculture. Research on the development of treatments or vaccines uses experimental challenges where salmon is exposed to amoebae concentrations ranging from 500 to 5, 000/L. However, the water concentrations of N. perurans on affected salmon farms are much lower. The lowest concentration of N. perurans previously reported to cause AGD was 10/L. Here, we report that concentrations as low as 0.1/L of N. perurans can cause AGD. We propose that concentrations of N. perurans that reflect those measured on salmon farms should be used for future experimental challenges.